Cerebrospinal fluid analysis for HIV replication and biomarkers of immune activation and neurodegeneration in long-term atazanavir/ritonavir monotherapy treated patients. Issue 28 (July 2016) - Ferretti, Francesca; Bigoloni, Alba; Passeri, Laura; Galli, Laura; Longo, Valeria; Gerevini, Simonetta; Spagnuolo, Vincenzo; Gisslen, Magnus; Zetterberg, Henrik; Fuchs, Dietmar; Cattaneo, Dario; Caramatti, Giada; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Cerebrospinal fluid (CSF) viral escape is a concern in ritonavir-boosted protease inhibitors monotherapy. The aim was to assess HIV-RNA, biomarkers of immune activation and neurodegeneration, and atazanavir concentrations in CSF of patients on successful long-term atazanavir/ritonavir (ATV/r) monotherapy. Methods: This is a substudy of the multicentric, randomized, open-label, noninferiority trial monotherapy once a day with atazanavir/ritonavir (NCT01511809), comparing the ongoing ATV/r along with 2 nucleoside retrotranscriptase inhibitors (NRTIs) regimen to a simplified ATV/r monotherapy. Patients with plasma HIV-RNA < 50 copies/mL after at least 96 study weeks were eligible. We assessed HIV-RNA, soluble (s)CD14, sCD163, CCL2, CXCL10, interleukin-6, and YKL40 by enzyme-linked immunosorbent assay; neopterin, tryptophan, kynurenine, and neurofilament by immunoassays; and ATV concentrations by liquid chromatography–mass spectrometry in paired plasma and CSF samples. Variables were compared with Wilcoxon rank-sum or Fisher exact test, as appropriate. Results: HIV-RNA was detected in the CSF of 1/11 patients on ATV/r monotherapy (114 copies/mL), without neurological symptoms, who was successfully reintensified with his previous 2NRTIs, and in none of the 12 patients on ATV/r + 2NRTIs. CSF biomarkers and ATV concentrations did not differ between the 2 arms. Conclusions: CSF escape was uncommon in patients on long-term ATV/r monotherapy and was controlled with reintensification.